Formulation and invitro evaluation of albendazole nanosuspensions - Mothkuri Sathish Kumar (International Journal of Pharmacy and Analytical Research, 2022)
Albendazole is an BCS class II drug is a broad-spectrum anthelmintic structurally related to mebendazole that is effective against many diseases. It is successfully used in experimental and clinical chemotherapy of different intestinal and systemic parasitosis. Its efficacy is often limited by poor intestinal absorption due mainly to its low aqueous solubility. Efficacy of albendazole can be enhanced by improving its dissolution. Reduction in particle size to Nano scale can help in dissolution improvement by increase in surface area. Due to its high half-life it can be formulated as a Nano suspension. Nano suspension is a novel technique used to increase the solubility of the drug prepared by solvent evaporation method. The Nano suspensions are novel promising target and controlled released dosage form which is gaining importance because of ease of manufacturing and diversified applications. The present trend of pharmaceutical research lies in the usage of biodegradable polymer because of its availability and low toxicity. Nanosuspension containing drug was prepared by solvent evaporation method by using combinations of Tween 80, Polaxomer, PVP-K90, PVA, and Acetone and quantity sufficient water). Estimation of Albendazole was carried out spectrophotometrically at 246nm. The Nano suspension were evaluated for parameters such as drug content uniformity, scanning electron microscopy, particle size analysis, zeta potential, in-vitro release, short-term stability, drug excipient interactions (FTIR). The stability data was also subjected to statistical analysis. The drug release from the Nanosuspension was explained by the using mathematical model equations such as zero order, first order, and equation methods. Based on the regression values it was concluded that the optimized formulation F9 follows Zero order kinetics.